PENINGKATAN AKTIVITAS DAN HASIL BELAJAR TARI MELALUI METODE TUTOR SEBAYA DI SDN 05 KOTA BENGKULU - Elfa Zarnita; Nike Anggraini (Universitas Sriwijaya, 2020)
This study aims to determine the increase in activity and student learning outcomes in dance subjects through the Peer Tutor Method for students of SDN 05 Kota Bengkulu. The research was conducted in February 2019. The subjects in this study were class Va. The methods used in collecting data are observation, interview and documentation. This research is a classroom action research using 2 cycles. Each cycle consists of four stages, namely: planning, implementing actions, observing and reflecting and evaluating. The instruments used were observation sheets, research sheets, questionnaire, interview guidelines and field notes. The results showed that there was an increase in activity and student learning outcomes in class Va SDN 05 Bengkulu City. The increase in students can be seen from the increase in the quality of the learning process as shown by the increase in learning outcomes, enthusiasm and activeness of students when participating in learning. The improvement of the learning process is seen from an increase in the score and the average learning outcomes before and after the action is taken. The average value before the action was 46.18. In the first cycle the average increased to 65.78 and in the second cycle it increased to 82.65. The average increase has increased by 36.47 and fulfills the minimum passing grade (KKM) 75. From the results of this study, it is known that through the sebay tutor method, the activity and learning outcomes of SDN 05 Bengkulu City students in class Va. Keywords: Activities, Dance Learning Outcomes, Peer Tutors